Sejarah Perkembangan Kurikulum di Indonesia - Putri, Desi Sandra; Marzelni, Marzelni; Delastri, Yefrineng; Anggraini, Desi; Demina, Demina; Darmansyah, Darmansyah (Jurnal Ilmiah Wahana Pendidikan, 2025)
The aim of writing this article is to explain the history of curriculum development in Indonesia. This scientific journal presents material related to curriculum development in Indonesia from the colonial era to independence, then analyzes it and presents it systematically in this paper. The results of this article present the history of curriculum development in Indonesia.